Pixaura: supporting tentative decision making when selecting and sharing digital photos - Elgart, Benjamin; Kamppari, Saara; Lewis, Bridget; Prasad, Ajay; Rhee, Yong Woo; Satpathy, Lalatendu; Drucker, Steven (Proceedings of the 22nd British CHI Group Annual Conference on HCI 2008: People and Computers XXII: Culture, Creativity, Interaction - Volume 2, 2008)
Current advances in digital technology promote capturing and storing more digital photos than ever. While photo collections are growing in size, the amount of time that can be devoted to viewing, managing, and sharing digital photos remains constant. Photo decision-making and selection has been identified as key to addressing this concern.